20-Hydroxyecdysone protects against oxidative stress-induced neuronal injury by scavenging free radicals and modulating NF-κB and JNK pathways. - Jun Hu (Public Library of Science (PLoS), 2012)
Oxidative stress plays an important role in the pathological processes of ischemic brain damage. Many antioxidants have been shown to protect against cerebral ischemia injury by inhibiting oxidative stress both in vitro and in vivo. 20-Hydroxyecdysone (20E), an ecdysteroid hormone, exhibits antioxidative effects. For the work described in this paper, we used an in vitro oxidative damage model and an in vivo ischemic model of middle cerebral artery occlusion (MCAO) to investigate the neuroprotective effects of 20E and the mechanisms related to these effects. Treatment of cells with H(2)O(2) led to neuronal injury, intracellular ROS/RNS generation, mitochondrial membrane potential dissipation, cellular antioxidant potential descent, an increase in malondialdehyde (MDA) and an elevation of intracellular [Ca(2+)], all of which were markedly attenuated by 20E. Inhibition of the activation of the ASK1-MKK4/7-JNK stress signaling pathway and cleaved caspase-3 induced by oxidative stress were involved in the neuroprotection afforded by 20E. In addition, 20E reduced the expression of iNOS protein by inhibition of NF-κB activation. The neuroprotective effect of 20E was also confirmed in vivo. 20E significantly decreased infarct volume and the neurological deficit score, restored antioxidant potential and inhibited the increase in MDA and TUNEL-positive and cleaved caspase-3-positive cells in the cerebral cortex in MCAO rats. Together, these results support that 20E protects against cerebral ischemia injury by inhibiting ROS/RNS production and modulating oxidative stress-induced signal transduction pathways.